Root trunk height as a risk factor for periodontal furcation involvement in maxillary first molars: an in vitro study. - Porciúncula, Hélio Ferraz; Zuza, Elizangela Partata; da Porciúncula, Mariana Machado; de Toledo, Benedicto Egbert Corrêa; Mendes, Ary José Dias (My University, 2007)
The aim of this study was to correlate the root trunk height from the furcation openings on the buccal, mesial and distal surfaces to the cemento-enamel junction in upper first permanent molars in human beings with risk for periodontal disease progression. One hundred extracted maxillary first molars were used. Reference points and demarcations were determined from the entrance of the buccal (F1), mesial (F2) and distal (F3) furcations to the cemento-enamel junction in millimeters. The mean distances found were 3.50 mm, 4.44 mm and 4.26 mm for the buccal, mesial and distal furcations, respectively, in relation to the cemento-enamel junction. The statistical analyses were Student's t-test and Chi-square (X2). With periodontal disease progression, the buccal furcation presents a greater compromising risk due to its proximity to the cemento-enamel junction, while the mesial furcation is the most distant, comprising a lesser risk.
Keywords: chi square distribution; confidence interval; disease course; human; molar tooth; pathology; periodontal disease; tooth cervix; tooth root; Chi-Square Distribution; Confidence Intervals; Disease Progression; Humans; Molar; Periodontal Diseases; Tooth Cervix; Tooth Root